MODERN APPROACHES AND METHODS OF PHYSICAL THERAPY IN REHABILITATION OF CHILDREN WITH CEREBRAL PALSY IN THE CONDITIONS OF CLINICAL PSYHONEUROLOGICAL SANATORIUM - Галиева, Галина Юрьевна; Панченко, Татьяна Николаевна; Валуева, Инна Владимировна; Ревтова, Наталья Владимировна; Лариков, Андрей Викторович (Medicine in Kuzbass, 2018)
The problems of patients with cerebral palsy affect various areas of health and activity, therefore, the assistance provided by specialists should be comprehensive, aimed at the prevention and treatment of complications of the disease, the development of the child’s capabilities and the creation of optimal conditions in which he can realize his potential. The choice of the goal of rehabilitation, in addition to the child’s age, should be based on the severity of the child’s impairments according to the scale of the GMFCS (Gross Motor Function Classification System) -system of classifications of large motor functions. This article highlights the effectiveness of rehabilitation interventions using a problem-oriented approach.